2019
DOI: 10.1101/512103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic dissection of femoral and tibial microarchitecture

Abstract: Our understanding of the genetic control of bone has relied almost exclusively on estimates of bone mineral density. In contrast, here we have used high-resolution x-ray tomography (8 µm isotropic voxels) to measure femoral and tibial components across a set of ~600 mice belonging to 60 diverse BXD strains of mice. We computed heritabilities of 25 cortical and trabecular compartments. Males and females have well matched trait heritabilities, ranging from 0.25 to 0.75. We mapped 16 QTLs that collectively cover … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 126 publications
(157 reference statements)
0
7
1
Order By: Relevance
“…In contrast to our findings, Lu and colleagues ( 13 ) did not find any QTL in males. We believe several factors make our study more reliable than the Lu and colleagues ( 13 ) study, including: (i) strict control of environmental conditions and diet, (ii) careful balancing of RI lines across mouse shipments, (iii) use of a body size correction ( 26 ) to account for size differences among the BXD lines, (iv) better line estimates due to more replicates within lines (mean 7.72 ± 0.78, median = 8 versus mean [males] 4.64 ± 2.67, median = 4), and (v) use of a very narrow harvest age window (mean = 85 days; range 81–91 days versus mean [males] = 96 days; range 50–375 days). Although Lu and colleagues ( 13 ) attempted to statistically adjust for age in their analysis, trabecular bone mass (BV/TV) in mouse long bones increases 30% from 2 to 4 months of age and then drops by more than 60% by 12 months of age, ( 76 ) so this correction may not have been effective.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, Lu and colleagues ( 13 ) did not find any QTL in males. We believe several factors make our study more reliable than the Lu and colleagues ( 13 ) study, including: (i) strict control of environmental conditions and diet, (ii) careful balancing of RI lines across mouse shipments, (iii) use of a body size correction ( 26 ) to account for size differences among the BXD lines, (iv) better line estimates due to more replicates within lines (mean 7.72 ± 0.78, median = 8 versus mean [males] 4.64 ± 2.67, median = 4), and (v) use of a very narrow harvest age window (mean = 85 days; range 81–91 days versus mean [males] = 96 days; range 50–375 days). Although Lu and colleagues ( 13 ) attempted to statistically adjust for age in their analysis, trabecular bone mass (BV/TV) in mouse long bones increases 30% from 2 to 4 months of age and then drops by more than 60% by 12 months of age, ( 76 ) so this correction may not have been effective.…”
Section: Discussioncontrasting
confidence: 99%
“…( 43 ) The largest of these studies was conducted by Lu and colleagues ( 13 ) who used 61 BXD RI lines in a mapping study to identify QTL for femoral and tibial μCT phenotypes in female and male mice aged 50 to 375 days. In contrast to our findings, Lu and colleagues ( 13 ) did not find any QTL in males. We believe several factors make our study more reliable than the Lu and colleagues ( 13 ) study, including: (i) strict control of environmental conditions and diet, (ii) careful balancing of RI lines across mouse shipments, (iii) use of a body size correction ( 26 ) to account for size differences among the BXD lines, (iv) better line estimates due to more replicates within lines (mean 7.72 ± 0.78, median = 8 versus mean [males] 4.64 ± 2.67, median = 4), and (v) use of a very narrow harvest age window (mean = 85 days; range 81–91 days versus mean [males] = 96 days; range 50–375 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human genome-wide association studies (GWAS) identified GREM2 variants associated with developmental disorders and disease, such as bone function and bone mass associated with osteoporosis, atrial fibrillation, and tooth agenesis (9)(10)(11)(12)(13). A Grem2 -/mouse line was previously developed as part of a high-throughput mouse knockout and phenotyping project (14).…”
Section: Introductionmentioning
confidence: 99%
“…GREM2 tightly associates with heparin through a protein binding domain outside of the BMP binding domain, which limits or downregulates BMP signaling, thus enhancing the inhibitory activity of GREM2 on BMPs (2,8). Human genome-wide association studies (GWAS) identified GREM2 variants associated with developmental disorders and disease, such as bone function and bone mass associated with osteoporosis, atrial fibrillation, and tooth agenesis (9)(10)(11)(12)(13). A Grem2 -/mouse line was previously developed as part of a high-throughput mouse knockout and phenotyping project (14).…”
Section: Introductionmentioning
confidence: 99%